EFFECTIVENESS OF LEGAL PROTECTION AGAINST CHILD CRIMES POLICY ANALYSIS AND IMPLEMENTATION IN WEST JAVA - Juarsa, Juarsa; Santoso, Imam; Makbul, Agung (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2025)
The concept of resolving criminal cases through alternative methods has existed since the Dutch colonial era, as seen in Article 82 of the Indonesian Penal Code (KUHP), which allowed charges to be dismissed if the offender paid a voluntary fine (afkoop). Over time, practices like diversion for children and seponering by the Attorney General in the public interest evolved, indicating early forms of restorative justice within the Indonesian legal system. This article explores the application, principles, and integration of restorative justice in criminal procedure law. It suggests that restorative justice is especially effective for minor offenses or cases with limited financial impact, emphasizing healing, voluntary participation, and social responsibility. For restorative justice to thrive, the legal system must shift from punishment to recovery, making it crucial for the development of a more humane and socially just criminal justice system.